2017
DOI: 10.4236/ajac.2017.83015
|View full text |Cite
|
Sign up to set email alerts
|

FTIR-ATR and FT-Raman Spectroscopy for Biochemical Changes in Oral Tissue

Abstract: Nowadays, biomedicine development is caused by the necessity of fast premalignant and malignant diagnosis. In the case of cancer, it is important to identify degree of tumor's malice. We investigated the differences of Fourier Transform Infrared-Attenuated Total Reflection (FTIR-ATR) and FT-Raman spectroscopy between leukoplakia, oral cancer and normal tissues. Human tissue contains many compounds with known absorption spectra in the range of Near Infrared (NIR) spectroscopy. These compounds have a fingerprint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…A number of new cases (275,000) are recorded yearly, mainly in developing countries, due to the population habits to use carcinogens, such as tobacco and betel quid. Oral squamous cell carcinoma (OSCC), identified in all oral cancer cases, develops from visible oral mucous membrane lesions like leukoplakia (OLK) and erythroplakia [137,138,139,140,141,142,143,144,145,146,147,148,149]. Other forms of oral precancer or premalignant lesions are oral submucous fibrosis (OSF), tobacco pouch keratosis, or lichen planus (OLP) [140].…”
Section: Drifting From Molecular To Clinical Practicementioning
confidence: 99%
See 1 more Smart Citation
“…A number of new cases (275,000) are recorded yearly, mainly in developing countries, due to the population habits to use carcinogens, such as tobacco and betel quid. Oral squamous cell carcinoma (OSCC), identified in all oral cancer cases, develops from visible oral mucous membrane lesions like leukoplakia (OLK) and erythroplakia [137,138,139,140,141,142,143,144,145,146,147,148,149]. Other forms of oral precancer or premalignant lesions are oral submucous fibrosis (OSF), tobacco pouch keratosis, or lichen planus (OLP) [140].…”
Section: Drifting From Molecular To Clinical Practicementioning
confidence: 99%
“…Naurecka et al [145] compared in 2017 the FTIR-ATR and FT-Raman absorption spectra of abnormal (OLK and oral cancer) and normal tissues in the main regions of lipid (2800–3000 cm −1 ), protein (1500–1700 cm −1 ), and nucleic acids (1000–1250 cm −1 ), pointing out the OLK “fingerprint region” is in the range of 900–1800 cm −1 . The FTIR spectrum revealed the following modifications: the absorption peak at 1238 cm −1 is correlated with nucleic acids symmetrical stretching, the phosphate wavenumbers were notable lower compared with that of normal tissue, and the shifting of the 1030 cm −1 band was ascribed to –CH 2 OH vibrations (1024 cm −1 for OLK and 1030 cm −1 for cancer/normal tissue).…”
Section: Drifting From Molecular To Clinical Practicementioning
confidence: 99%
“…Bruni et al reported increased DNA, lipid, and collagen levels in OSCC samples [45]. However, their attribution of the 1026 cm −1 band to collagen is debatable, as many other studies assigned the same band to glycogen instead [47][48][49][50]. Sabbatini et al performed vibrational analyses of both epithelial and connective tissues of OSCC at various malignancy grades (G1-G3) and identified potential spectral markers for oral carcinogenesis, including the increase of free glycogen levels, structural alterations in nucleic acids, and a higher amount of RNA, which suggests an increase of the cellular transcriptional activity [51].…”
Section: Discussionmentioning
confidence: 99%
“…[48]. Naurecka et al used the FTIR-ATR technique to study normal, leukoplakia, and cancerous oral tissues and reported spectral differences at amide I at 1650 cm −1 , amide II at 1535 cm −1 , nuclei acids at 1238 cm −1 , and glycogen at 1024-1030 cm −1 [49].…”
Section: Discussionmentioning
confidence: 99%
“…Naurecka et al investigated the differences of FTIR-ATR and FT-Raman spectroscopy among leukoplakia, oral cancer, and normal tissues. FTIR spectral differences were observed at 1238 cm −1 (related to phosphate stretching in nucleic acids) between normal and cancer tissues and at 1030 cm −1 (related to –CH 2 OH vibration in glycogen) among normal, leucoplakia, and cancer tissues [ 94 ].…”
Section: Ftir For Oral Cancer Diagnosismentioning
confidence: 99%